Analisa Faktor-Faktor yang Mempengaruhi Penerapan Konservatisme Akuntansi pada Perusahaan Real Estate yang Terdaftar Di Bursa Efek Indonesia Tahun 2012 – 2016 - Aang Sugianto; Pratana Puspa Midiastuty (JURNAL FAIRNESS, 2022)
The study aims to examine the effect of company size, capital investment, litigation, institutional ownership structure growth opportunity, tax. Against accounting conservatism this study population is all real estate companies listed on the Indonesia stock exchange in 2012-2016. The sample is determined based on the method purposive sampling, so as many as 45 companies were sampled. With a total of 225 observation data analysis techniques using multiple linier regression analysis with accounting conservatism as the dependent variable. Company size, capital investment, litigation, institutional ownership, structure, growth opportunity has no influence on accounting conservatism, which has an influence on accounting conservatism is only tax planing.   The study aims to examine the effect of company size, capital investment, litigation, institutional ownership structure growth opportunity, tax. Against accounting conservatism this study population is all real estate companies listed on the Indonesia stock exchange in 2012-2016. The sample is determined based on the method purposive sampling, so as many as 45 companies were sampled. With a total of 225 observation data analysis techniques using multiple linier regression analysis with accounting conservatism as the dependent variable. Company size, capital investment, litigation, institutional ownership, structure, growth opportunity has no influence on accounting conservatism, which has an influence on accounting conservatism is only tax planing.